Electrokinetic technique for water treatment - Tan, Reuben (2019)
The study aims to reflect the key analysis of disinfection using electric fields within a micro-channel. We want to investigate if different sources -alternating or direct current, conductivity, flow rate, shape of micropillars, frequency, voltage and current will affect the rate of disinfection in water bodies. Experimentation was conducted on the microdevices that have been fabricated using photolithography techniques. The microchannel has 2 points, the inlet and outlet. A flow of electrolyte containing bacteria is being pumped constantly into the microchannel; and an electrical source is being supplied to the microchannel between 2 electrodes. Within the electrical field, bacteria will be inactivated and collected at the end of the channel. This is carried out with different parameters as mentioned. From the results obtained, AC is less effective in disinfecting cells compared to DC. This is due to the greater electroporation rate with DC supply. However, as AC does not contribute to any complications to the microchannel during the process, it can be considered as a more appropriate electrical source. It not only kills bacteria effectively, but it does contribute to any complications to the microchannel during the process. It is also concluded that conductivity plays the largest role. Not only does it increase the current within the microchannel, but it enables the bacteria to be killed more effectively. Increasing voltage would be proportionate to increasing current, however, this might change due to the non-uniformity of conductance within the electrolyte. The shape of the micropillars plays an important role and the frequency of the AC source can contribute to a more exposure time when it comes to the disinfection of bacteria within the water. With the experimentations for the flow rates we used, they do not affect the inactivation within the microchannel.